Between mars and venus: Peter the great in northern German cities and duchies in 1716 Entre mars et vénus: Pierre le grand dans les villes et du duchés du nord de l'allemagne (1716) - Félicité, Indravati (Quaestio Rossica, 2018)
Peter the Great's journey around Northern Germany in 1716 was characterised by a war that had agitated the Baltic from the beginning of the century and by diplomatic negotiations that aimed to provide the Romanov dynasty with strong European ties. The cities and duchies of the northern Holy Empire were at the intersection of these goals. In the context of geopolitical reorganisation caused by the Great Northern War, the dukes of Mecklenburg-Schwerin and Schleswig-Holstein-Gottorp were interested in finding a new protector for their defenceless territories in face of the threat posed by the three traditional northern powers, Sweden, Denmark, and Brandenburg. The northern cities, too, played an important role in the tsar's commercial projects because after the Thirty Years' War, a phase of Swedish supremacy had begun in the Baltic when those cities had been an impenetrable barrier between Russia and Western European and Atlantic trade. Furthermore, it is a little known but important fact that most of the cities visited by the imperial Russian couple were princely residences or cultural centres of European outreach. In this respect, the places Peter I and his spouse Catherine stayed in help us to better understand interactions between the Russian government and the interlocutors that they met during their journey. This paper is based on unpublished documents kept in the archives of Lübeck and Schwerin and on journals of that period: these allow the author to analyse the complexity and diversity of German reactions to the presence of the tsar in this region. By fuctuating between military actions and matrimonial festivities, this journey also reveals the ambiguous perception of Russia by observers.
CRIS-Team Scopus Importer:2024-04-04
Keywords: Baltic Sea; Diplomacy; Great Northern War; Hansa; Holy Roman Empire; Lübeck; Mecklenburg-Schwerin